2017
DOI: 10.30554/archmed.17.2.1929.2017
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización epidemiológica de pacientes con Sepsis Neonatal en un hospital de la ciudad de Cali (Colombia), 2014

Abstract: Objetivo: La infección neonatal se encuentra como la principal causa de fallecimientos neonatales en Colombia. El objetivo de este estudio fue establecer las características epidemiológicas de pacientes con sepsis neonatal reportados en un hospital de la ciudad de Cali. Materiales y métodos: Estudio de corte transversal analítico a partir de la revisión de 215 historias clínicas de neonatos diagnosticados con sepsis durante el 2014. Los factores de riesgo y su asociación con el desarrollo del tipo de s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Invasive mechanical ventilation was more common in men and in those who had a diagnosis related to sepsis/septic shock or trauma, all in line with the regional literature, which indicates sepsis as one of the main causes of admission to the ICU [ 1 , 14 ]. Other studies that have evaluated the characteristics of patients admitted for sepsis/septic shock or trauma have found a predominance of males [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Invasive mechanical ventilation was more common in men and in those who had a diagnosis related to sepsis/septic shock or trauma, all in line with the regional literature, which indicates sepsis as one of the main causes of admission to the ICU [ 1 , 14 ]. Other studies that have evaluated the characteristics of patients admitted for sepsis/septic shock or trauma have found a predominance of males [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Septic shock is a risk factor for in-hospital death. Worldwide, the mortality of hospitalized patients with sepsis/septic shock is 30–40% [ 21 , 22 ], and in Colombia, it is approximately 33% [ 15 ], which is high despite therapeutic efforts, and more so in patients who receive invasive mechanical ventilation, which is a population at high risk of complications such as cardiovascular collapse and cardiac arrest [ 23 ]. In the post-hoc analysis of the SEPSISPAM study, it was found that mortality, as well as vasopressor therapy and hospitalization time, was significantly higher in patients with sepsis who were intubated than in those who were not [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…So, currently, the recommendations for initial empirical antibiotic management are based on the etiological characterization identified by culture-dependent methods ( 20 – 22 ), and the targeted orientation of antimicrobial treatment is not achieved until the causal agent is identified in the culture. This situation can lead to non-specific treatment in patients with sepsis, unnecessarily exposing patients to broad-spectrum empirical antibiotics ( 18 , 23 ), increasing the risk of medical complications in the different age groups affected (example, necrotizing enterocolitis, invasive fungal infection), and the development of microbial resistance to antibiotics, alterations in the development of the intestinal microbiota, and death ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%